2015
DOI: 10.1063/1.4928544
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of GaSb(100) and its control studied by scanning tunneling microscopy and spectroscopy

Abstract: Atomic-scale knowledge and control of oxidation of GaSb(100), which is a potential interface for energy-efficient transistors, are still incomplete, largely due to an amorphous structure of GaSb(100) oxides. We elucidate these issues with scanning-tunneling microscopy and spectroscopy. The unveiled oxidation-induced building blocks cause defect states above Fermi level around the conduction-band edge. By interconnecting the results to previous photoemission findings, we suggest that the oxidation starts with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…We find this kind of similarity of desorption behavior unlikely for structures in which the difference is between Sb–(III/V) and O–(III/V) bonds in the topmost layers. Thus, we propose that either the O atoms are able to penetrate into the subsurface of the structure, similarly as in refs 42,44,45 [for GaSb/InSb(100)], and 46,47 [for Si(111) and (100)], or, that oxidation results in removal of In as In 2 O molecules and concomitant stabilization of (2 × 2)-Sb.…”
Section: Resultssupporting
confidence: 58%
“…We find this kind of similarity of desorption behavior unlikely for structures in which the difference is between Sb–(III/V) and O–(III/V) bonds in the topmost layers. Thus, we propose that either the O atoms are able to penetrate into the subsurface of the structure, similarly as in refs 42,44,45 [for GaSb/InSb(100)], and 46,47 [for Si(111) and (100)], or, that oxidation results in removal of In as In 2 O molecules and concomitant stabilization of (2 × 2)-Sb.…”
Section: Resultssupporting
confidence: 58%
“…Many studies were dedicated to the thermal, anodic and plasma oxidation of III-V semiconductor [17]. Early works on anodic oxidation of GaSb [18,19] and on native oxide films [20] were pursued [21] and till now the oxidation process of GaSb is studied experimentally [22] and theoretically [23]. In a recent work, the role of H 2 O 2 and H 2 O in GaSb reduction-oxidation reactions was investigated in detail [24].…”
Section: Introductionmentioning
confidence: 99%
“…Further insight in the oxidation reaction mechanism at the semiconductor/oxygen interface was recently obtained by scanning tunneling microscopy measurements which exploited the controlled exposure of a clean GaSb surface to oxygen [25]. The research on the reaction mechanism at GaSb/ solution interfaces is ongoing and a recent study has shown that the redox processes are relevant for modifying the surface's electronic structure of GaSb during the reaction with an aqueous sodium sulfide solution [26].…”
Section: Introductionmentioning
confidence: 99%